IMPLANTACIÓN DE CONTABILIDAD DE COSTOS POR ÓRDENES DE PRODUCCIÓN EN LA EMPRESA PROARCI DE LA CIUDAD DE ZAMORA EN EL PERIODO CORRESPONDIENTE DEL 01 DE ENERO AL 31 DE MARZO DEL 2014 - Chamba Poma, Johanna Elizabeth (2015)
This thesis entitled: "IMPLEMENTATION OF COST ACCOUNTING FOR ORDERS PRODUCTION IN THE COMPANY PROARCI CITY OF ZAMORA IN THE RELEVANT PERIOD 01 JANUARY TO 31 MARCH 2014", whose objectives were aimed at: First design the necessary documents in the system of production costs orders in manufacturing clay products that will maintain control of the three elements of cost; the data bank cards are used to track the entry and exit of raw material used in the manufacturing process, requisition orders in which the raw material required detailed handled; control workers regarding labor time cards and thus develop the worksheet detailing the time spent on each production order was used, and finally a budget that allowed distributed as prepared the cost of direct materials Manufacturing Indirect Costs. Second implement an accounting process starting with the development of the inventory in which the values, goods, duties and obligations, once organized the source documentation is reflected, we proceeded to make the Plan and Manual of Auditors, to the initial situation, then accounting entries were recorded in Daybook, then the biggest of the accounts submitted were developed, Balance, Worksheet, the respective adjustments and Financial Statements; and finally Financial Indicators, soundness and profitability was applied to their analysis. In conclusion it is determined that the company was limited to simple annotations and implement cost accounting for production orders has been able to determine the unit cost and the total cost of generating product, also a utility; further analysis should be performed to verify that it is properly using the three elements of cost and seek strategies to improve production.